O papel da branquitude na hierarquização das raças : construção e validação de escala - Oliveira, Rita de Cassia de Jesus (2023)
Whiteness can be defined as characteristics of white identity constructed through participation in a culture steeped in white supremacist ideologies. Based on these ideologies, the white group has created and maintained attitudes that guarantee symbolic and material power, called white privilege in the literature on the subject, which is characterized by the appropriation of illegitimate resources and produces racial inequality. To maintain this situation, whiteness has strategies such as: white invisibility, that is, the non-perception of whites as people of race, so that whites are the norm and those who have race are others; the white group does not reflect on its participation in racial inequalities and attributes this problem to other factors, such as slavery in Brazil; in this context, miscegenation is always cited as a mechanism to confirm this supposed neutrality. Therefore, this dissertation has been divided into three chapters. The first chapter addresses conceptual issues related to whiteness: white privilege, white ignorance, and white fragility, as well as the historical development of whiteness studies. The second chapter provides an integrative overview of whiteness studies in Brazil. For this purpose, a search was conducted in the Psycinfo, VHL Psi, SciELO and CAPES journals databases, using the term “whiteness” as a keyword. The initial search identified 200 publications; after applying the filters, the number was reduced to 12 works. The results show that the topic of "whiteness" is of interest to several fields, although there are still many aspects to be explored. From the theories and concepts used in the articles, race, racism, miscegenation, whiteness, and racial democracy can be highlighted. As for the theoretical gaps, no quantitative studies were found, indicating the need to conduct more systematic and representative studies of the national population. Finally, the third chapter consists of a study aimed at creating and validating a scale to measure the degree of whiteness in the Brazilian population. This study included a community sample of 653 subjects, half of whom were used for exploratory factor analysis (AFE) and half for confirmatory factor analysis (CFA). Principal axis analysis (PAF) revealed that Bartlett sphericity tests were significant [χ²(171) = 1503.12; p < 0.001] and KMO = 0.86, indicating the interpretability of the correlation matrix of the items. Factor loadings varied from 0.11 to 0.74, and items with loadings less than 0.30 were removed (items 4, 8, 14, 15, 16, and 17). Thus, the single-factor version of the scale was composed of 13 items with loadings ranging from 0.347 to 0.743. Positive items theoretically refer to critical whiteness, whereas negative items refer to noncritical whiteness. The internal consistency of the general factor was satisfactory (ω = 0.86). A confirmatory factor analysis (CFA) was then conducted with the other half of the sample. The single-factor structure showed good fit indicators: χ² = 98.19; gl = 65; p < 0.001, with χ²/gl = 1.38; CFI = 0.99; TLI = 0.99; RMSEA = 0.031; 90% CI [0.017; 0.043]; SRMR = 0.068. Factor loadings varied between 0.30 (item 12) and 0.80 (item 1). Internal consistency for this subsample was adequate (ω = 0.86). The results indicate a low level of whiteness, which may be related to the characteristics of the sample. The need for further research using a quantitative approach is indicated.